Coordination polymers constructed from tetrahedral-shaped adamantane tectons. Issue 1 (9th December 2016) - Mocanu, Teodora; Pop, Lidia; Hădade, Niculina D.; Shova, Sergiu; Grosu, Ion; Andruh, Marius
Abstract : Two coordination polymers with different dimensionalities have been constructed using rigid tetrahedral organic tectons derived from adamantane. Abstract : Two rigid tetrahedral organic linkers derived from adamantane have been employed in constructing a 3-D, 4-fold interpenetrated framework featuring a PtS topology, [CuL 1 (H2 O)2 ](BF4 )2 ·8H2 O (1 ) (L 1 = 1, 3, 5, 7-tetrakis4-(4-pyridyl)phenyladamantane), and a 2-fold interpenetrated grid-like coordination polymer, [Mn(hfac)2 (L 2 )0.5 ] (2 ) (L 2 = 1, 3, 5, 7-tetrakis(4-cyanophenyl)adamantane).